Management of peptic ulcer perforations: Comparison of open and laparoscopic procedures - (:unkn) unknown (My University, 2019)
Introduction: Peptic ulcer perforation requires urgent surgical intervention, but there is no consensus on apreference for open or laparoscopic surgery. The aim of this study was to compare the results of laparoscopic and open methods of surgery for patients with a peptic ulcer perforation.Materials and Methods: The data of 52 patients who underwent surgery for peptic ulcer perforation at 4hospitals were investigated retrospectively. The patients were divided into 2 groups according to the surgical technique applied: open surgery or laparoscopic. Both techniques used an omental patch to repair the perforation. Patient age, gender, preoperative blood white blood cell count, blood amylase level, duration of symptoms before admission to the hospital, length of operation, number of drains, quantity of intra-abdominal free fluid observed during the operation, quantity of fluid used for irrigation, patient abdominal operation history, and complications were noted and analyzed.Results: Thirty-seven of the patients underwent open surgery and 15 underwent laparoscopic surgery (meanage: 37.73±16.85 years; female/male 3/49). There was no signifiant difference in the parameters betweenthe groups. No mortality was observed in any of the patients. Wound infection developed in 2 patients whowere operated on using the open technique. Only 1 case of laparoscopic surgery (6.66%) was converted to open surgery.Conclusion: Laparoscopic repair of a peptic ulcer perforation demonstrated results that were similar to opensurgery and helps to reduce complications such as wound infection. It may be especially valuable in earlyonset cases and younger patients.
Keywords: Gastroenteroloji ve Hepatoloji; Genel ve Dahili Tıp; Cerrahi